(untitled) (International journal of medical sciences, 2025)
Objective: To evaluate the clinical efficacy of an optimized therapeutic protocol incorporating an enkephalinase inhibitor (Racecadotril) and Zinc supplementation compared to standard oral rehydration therapy alone in children hospitalized with acute seasonal viral gastroenteritis. Methods: A prospective, open-label, randomized controlled trial was conducted at the [Name of Infectious Disease Hospital] during the peak viral season (November 2023 – March 2024). The study enrolled 200 children aged 6 months to 5 years with confirmed viral gastroenteritis (Rotavirus or Norovirus antigen-positive). Patients were randomized 1:1 into two groups: Control Group (n=100): Received standard World Health Organization (WHO) protocol: Low-osmolarity Oral Rehydration Solution (ORS) and diet. Intervention Group (n=100): Received standard care (ORS) + Pathogenetic Therapy (Racecadotril 1.5 mg/kg TID) + Symptomatic support (Zinc sulfate 20mg OD). Primary outcomes were the duration of diarrhea (time to the last unformed stool) and total volume of ORS consumed. Secondary outcomes included the length of hospital stay (LOS) and the rate of treatment failure requiring IV rehydration. Results: The Intervention Group demonstrated a significantly shorter median duration of diarrhea compared to the Control Group (36.4 hours vs. 58.2 hours; p<0.001). The total recovery time was reduced by approximately 22 hours. Consequently, the mean Length of Stay (LOS) was significantly shorter in the Intervention Group (2.8 ± 0.6 days vs. 4.1 ± 0.9 days; p<0.001). The requirement for unscheduled intravenous fluid resuscitation was lower in the Intervention Group (4% vs. 12%; p=0.03). Subgroup analysis revealed that Racecadotril was equally effective for both Rotavirus and Norovirus etiologies. Conclusion: An optimized treatment strategy combining standard rehydration with pathogenetic antisecretory therapy (Racecadotril) and mucosal regeneration support (Zinc) is superior to rehydration alone. This approach actively reduces fluid loss and shortens disease duration without safety concerns, suggesting it should be the standard of care for seasonal viral gastroenteritis.